Red lightning - Bucci, Marco 1981-; Atzeni, Riccardo (Ablaze Publishing, 2022)
"It is a cold morning in January 2016, and thirty-year-old Samuel is ready to leave the house and live another day of his ordinary existence. As soon as he arrives on the street, he learns about David Bowie's death. The news strikes him so hard that he is stunned, and his are not moments of bewilderment, but hours, days, years, and centuries he finds himself catapulted across space and time. He soon discovers that society of the future is not so different from his own; is this the ultimate utopia or is there more to this perfect world?" --
Keywords: Bowie, David -- 1947-2016; Tod; Zeitreise; Junge -- 11-14 Jahre; Bowie, David / Death / Comic books, strips, etc / Fiction; Time travel / Comic books, strips, etc / Fiction; Gender identity / Comic books, strips, etc / Fiction; Death; Science fiction comics; Queer comics; Comics (Graphic works); Graphic novels; Comic